DESIGN OF WEB-BASED HEAD OF ENVIRONMENTAL PERFORMANCE INFORMATION SYSTEM APPLICATION (SIJALI) USING RAPID APPLICATION DEVELOPMENT (RAD) METHOD - Raipo, Ahmad Fariz; Elhanafi, Andi Marwan; Irwan, Dedy (Cattleya Darmaya Fortuna, 2025)
In the era of increasingly sophisticated information technology development like today, in accordance with the Vision and Mission of the Mayor of Medan, namely Medan Maju, a new breakthrough in the form of digital innovation is needed. Given the frequent accumulation of files from the report reports of each rank, both ASN, PHL, PPPSU, and the Head of the Environment. and often get complaints from the Head of the Environment behind the high intensity of their work in Medan Petisah District they must also make so many reports in hard copy form, so the author thought of facilitating the work of the Head of Environment while efficiently using Paper at the Medan Petisah Sub-District Office by designing a Web-Based Application namely the Head of Environment Performance Information System (SIJALI) using the Rapid Application Development (RAD) method, which later this application can be accessed with a smartphone or computer through a browser or in the form of a website.